2020
DOI: 10.3390/ma13092050
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone-Loaded Nanostructured Hybrid Material for Skin Ulcer Treatment

Abstract: Pioglitazone, a popular antidiabetic drug, which was recently shown to be effective in the treatment of skin ulcers, was successfully encapsulated in polysaccharide nanoparticles and used as a bioactive component of the wound-dressing material based on modified bacterial nanocellulose. Alginate and hydroxypropyl cellulose were used as a matrix for the nanoparticulate drug-delivery system. The matrix composition and particles’ size, as well as drug encapsulation efficiency and loading, were optimized. Pioglitaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Regarding the effects observed during the use of pioglitazone, it has been mainly reported that it increases insulin sensitivity, interference with lipid homeostasis, and regulation of the inflammatory response. Thus, many efforts have been made in the development of formulations for the topical use of pioglitazone ( Silva-Abreu et al., 2017 ; Nair et al., 2019 ; Rojewska et al., 2020 ), opening new expectations for the treatment of skin diseases such as CL. Indeed, patients with psoriasis treated with topical pioglitazone had a decreased severity in disease score ( Mittal et al., 2009 ; Singh and Anil, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects observed during the use of pioglitazone, it has been mainly reported that it increases insulin sensitivity, interference with lipid homeostasis, and regulation of the inflammatory response. Thus, many efforts have been made in the development of formulations for the topical use of pioglitazone ( Silva-Abreu et al., 2017 ; Nair et al., 2019 ; Rojewska et al., 2020 ), opening new expectations for the treatment of skin diseases such as CL. Indeed, patients with psoriasis treated with topical pioglitazone had a decreased severity in disease score ( Mittal et al., 2009 ; Singh and Anil, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence points to their potential role as add-on topical agents, but this remains far from certain. 21,22 In conclusion, the WβcSP pathway plays a role in all phases of wound healing. 6 Accordingly, perhaps we should start exploring potential ways of its therapeutic implication to improve DFU healing.…”
Section: Editorialmentioning
confidence: 93%
“…Experimental evidence points to their potential role as add-on topical agents, but this remains far from certain. 21,22…”
Section: Editorialmentioning
confidence: 99%
“…Therefore it can be considered for the treatment of post-operative wounds. The analogous formulation was used to encapsulate pioglitazone, an antidiabetic drug effective in skin ulcer treatment [ 152 ]. Chitosan had a beneficial effect on drug stability inside the particles and prolonged release up to 5 days.…”
Section: Complexed Delivery Systemsmentioning
confidence: 99%